2011
DOI: 10.1186/1471-2180-11-263
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sub-inhibitory antibiotics on fibronectin-mediated host cell adhesion and invasion by Staphylococcus aureus

Abstract: BackgroundStaphylococcus aureus is a well-armed pathogen prevalent in severe infections such as endocarditis and osteomyelitis. Fibronectin-binding proteins A and B, encoded by fnbA/B, are major pathogenesis determinants in these infections through their involvement in S. aureus adhesion to and invasion of host cells. Sub-minimum inhibitory concentrations (sub-MICs) of antibiotics, frequently occurring in vivo because of impaired drug diffusion at the infection site, can alter S. aureus phenotype. We therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…This could explain the lack of a linear relationship between the drug exposure required for efficacy and the MIC of the isolate causing the infection, particularly as repeated in vivo administration of the compound (as done in these studies) would result in exertion of this effect at regular intervals. It has already been reported for S. aureus that subinhibitory concentrations of certain antimicrobials can suppress virulence factor production (30), including production of alpha-toxin (31,32), increase susceptibility to phagocytosis (31), and modulate adherence to fibronectin (33,34). Given that antibacterial agents are often present at subinhibitory concentrations during the normal course of antibiotic therapy, these types of effects should perhaps be taken into account when evaluating the magnitude of the PK/PD indices against certain organisms.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain the lack of a linear relationship between the drug exposure required for efficacy and the MIC of the isolate causing the infection, particularly as repeated in vivo administration of the compound (as done in these studies) would result in exertion of this effect at regular intervals. It has already been reported for S. aureus that subinhibitory concentrations of certain antimicrobials can suppress virulence factor production (30), including production of alpha-toxin (31,32), increase susceptibility to phagocytosis (31), and modulate adherence to fibronectin (33,34). Given that antibacterial agents are often present at subinhibitory concentrations during the normal course of antibiotic therapy, these types of effects should perhaps be taken into account when evaluating the magnitude of the PK/PD indices against certain organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Additional references of that may be of interest include Rasigade et al ., ; Davies et al ., ; Christensen et al ., ; and Reeks et al .,.…”
Section: Workhop Summarymentioning
confidence: 94%
“…Additional references of that may be of interest include Rasigade et al, 2011;Davies et al, 2006;Christensen et al, 2011;and Reeks et al,2005. Part 3: Emergence, transmission, and persistence of antimicrobial resistance Mechanisms of resistance and resistance transfer. Numerous mechanisms for antimicrobial resistance have been identified, and the impact of these mechanisms appears to be both drugand pathogen-specific (Table 2).…”
Section: Part 2: Methodology and Interpretation Of Antimicrobial Testingmentioning
confidence: 99%
“…Not taken into account is any effect that the antibiotic may have at subinhibitory concentrations, a situation frequently encountered during the normal course of antibiotic therapy. Specifically in S. aureus, it has already been reported that subinhibitory concentrations of certain antibiotics can inhibit exoprotein production (28), including critical virulence factors, such as alpha-toxin (29,30), increase susceptibility to phagocytosis (29), and modulate adherence to fibronectin (31,32) and can even inhibit biofilm formation (33,34). These effects may be important in the successful treatment of S. aureus infections and should perhaps be taken into consideration in the selection of therapy (30).…”
Section: Discussionmentioning
confidence: 99%